Conceptual Review: Cultivating Learner Autonomy Through Self-Directed Learning & Self-Regulated Learning: A Socio-Constructivist Exploration - Kharroubi, Sara; ElMediouni , Abdeljabbar (International Journal of Language and Literary Studies, 2024)
This paper proposes a comprehensive framework for fostering learner autonomy (LA) in educational settings by integrating socio-constructivist principles with self-directed learning (SDL) and self-regulated learning (SRL). Emphasizing LA as both a learning process and a personal capacity, the framework draws on Vygotskian socio-cultural principles and Piagetian cognitive development. It underscores the importance of fostering LA in the contemporary "post-truth" classroom, where critical thinking and information literacy are paramount. Through analysis, three key insights emerge: socio-constructivism highlights the interplay between social interactions and individual cognitive development, SDL serves as the pathway to LA by empowering learners to control their learning, and SRL integrates metacognition for the metaliterate learner. Looking ahead, future research could explore effective pedagogical strategies, ensure learner agency and empowerment, and develop robust methods to assess LA and metaliteracy skills. By addressing these areas, educators can create environments conducive to cultivating self-directed, critical thinkers prepared for the challenges of the information age.